Low-cost Smart Architecture for Classroom Response System Using Raspberry: RaspCRS - Moulay Taj, A.; Abouhilal, A.; Taifi, N.; Antari, J.; Malaoui, A. (International Journal of Engineering and Technology, 2019)
The purpose of this paper is to present a low-cost architecture based on embedded systems for the operation of a Classroom Response System (CRS). In order to validate the proposed architecture, various tests were conducted with 30 students enrolled in a renewable energy master. As part of this study, a mobile-based CRS has been developed using web-based technologies that makes the system very easy to use in educational environments. It allows the teacher to interview students using multiple-choice questions, in order to test their understanding of a concept discussed in class, the results of a question are displayed in real time on the mobile of the teacher. This tool has a strategic character because it allows improving the image of our university, pursuing the paths of smart cities. The results of test show the advantages and limitations of this architecture.Â Â